2023
DOI: 10.3390/vaccines11020447
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibodies as Predictors of Vaccine Breakthrough Infection in Healthcare Workers Vaccinated with or without a Heterologous Booster Dose: A Cohort Study during the Third COVID-19 Wave in Peru

Abstract: We evaluated neutralizing antibody (NAbs) levels as a protective factor against vaccine breakthrough infection (VBI) in healthcare workers (HCWs) during the third COVID-19 wave in Peru. This retrospective cohort study employed the information from a private laboratory in Lima (Peru) of HCW who received only two BBIBP-CorV vaccines or (additionally) a heterologous booster with BNT162b2. We evaluated the association between the VBI and the levels of NAbs at 21, 90, 180, and 210 days after the BBIBP-CorV second d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It has been previously reported that high levels of RBD-specific IgG are correlated with high VNTs toward the SARS-CoV-2 wild-type strain [ 24 , 33 ] and that hu-1-induced antibodies partly cross-react with variants of concern [ 15 , 24 , 34 ]. However, functional assays, such as virus neutralization assays or molecular interaction assays, are especially useful for the measurement of antibodies protecting against virus infection [ 12 , 35 , 36 ]. Therefore, serum samples obtained from mice six weeks after the third immunization with the PreS-RBD fusion constructs were analyzed regarding their capacity to neutralize SARS-CoV-2 Omicron ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that high levels of RBD-specific IgG are correlated with high VNTs toward the SARS-CoV-2 wild-type strain [ 24 , 33 ] and that hu-1-induced antibodies partly cross-react with variants of concern [ 15 , 24 , 34 ]. However, functional assays, such as virus neutralization assays or molecular interaction assays, are especially useful for the measurement of antibodies protecting against virus infection [ 12 , 35 , 36 ]. Therefore, serum samples obtained from mice six weeks after the third immunization with the PreS-RBD fusion constructs were analyzed regarding their capacity to neutralize SARS-CoV-2 Omicron ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these mutations fail to alter their structure, but some can alter their sequencing and the composition of amino acids in essential proteins, which could give rise to new variants. Currently, multiple variants are circulating worldwide, many with mutations that decrease the effectiveness of vaccines against COVID-19, even with high NAbs titers [ 37 , 38 , 39 ]. The emergence of these variants has motivated the use of bivalent vaccines, which the Food and Drug Administration (FDA) has approved for the immunization of patients older than six months in the case of the Moderna vaccine and patients older than five years with the Pfizer-BioNTech vaccine [ 40 ].…”
Section: Discussionmentioning
confidence: 99%